Genome-Wide Identification and Expression Profiling of the COMMD Gene Family in Four Bivalve Molluscs - Chen, Xiaomei; Hu, Naina; Lian, Shanshan; Li, Luoan; Sun, Fengzhi; Zhang, Lingling; Wang, Shi; Bao, Zhenmin; Hu, Jingjie (Frontiers in Marine Science, 2022)
The COMMD gene family, highly conserved among multicellular eukaryotic organisms, plays important roles in a variety of biological processes, ranging from copper homeostasis, ionic transport, protein trafficking, NF-κB mediated transcription and cell proliferation. However, systematic identification, spatiotemporal expression and stress responsive patterns of COMMD genes remain obscure in molluscs. Here, we analyzed the characteristics of COMMD gene family in four bivalve molluscs, referring to both genome and extensive transcriptomic resources. Investigation of genomic signatures, functional domains as well as phylogenetic relationships was conducted, and ten single-copy members were identified in Yesso scallop, Zhikong scallop, Pacific oyster and the dwarf surf clam, respectively. Strong purifying selection was revealed for COMMD4. Higher expressions of most COMMDs were observed in hepatopancreas, besides which different tissue preference of COMMDs’ expression was found among four bivalves. Moreover, in the dwarf surf clam, the responses of COMMD members under stresses were found more sensitive in hepatopancreas than in gill, and MlCOMMD9 and MlCOMMD4 might be the good candidate stress indicator gene respectively for copper ion stress and V. Anguillarum infection. Our study would assist in better understanding for the evolution of COMMD gene family and provide valuable information for their innate immune roles in bivalve molluscs.